O PODCAST NA IMPLEMENTAÇÃO DA METODOLOGIA DE RESOLUÇÃO DE PROBLEMAS NO ENSINO MÉDIO - Jefferson Frois Pontin (2024)
This dissertation focuses on the analysis of the use of the podcast as a resource for implementing the Problem Solving Methodology and, to this end, it is based on the following question: what potential is there in the association of the aforementioned methodological and instrumental biases for the recomposition of the teaching-learning process of Mathematics knowledge objects in High School? In view of this, we sought to improve the understanding of the aspects of this methodology in the mathematical educational universe and study the pedagogical possibilities of implementing the podcast based on what was already explained in Pontin (2020) and the documentary guidelines of the Currículo Paulista and the National Common Curricular Base. Next, a survey was carried out, in light of the results obtained in the latest internal and external evaluations, of content and structuring skills that were out of date, capable of being part of a process of “learning recomposition” shaped by the highlighted thematic. To this end, two problem situations were produced, published both in print and in podcast episodes, one of which was aimed at a 1st grade class and the other at a 3rd grade high school class at a state school in the interior of São Paulo. The investigation, of a quantitative and qualitative nature, included the participation of students from these classes, who carried out the proposed activities and responded to two physical questionnaires: the first before and the second after contact with the problems. The results, in general, corroborate the potential studied in terms of stimulating protagonism and student interest in relation to contextualization, procedural organization and the application of knowledge, valuing interaction, cooperation and different styles of learning and expression. Keywords: High School. Problem Solving Methodology. Podcast. Learning Recomposition.